A role for industrial looms in craft research - Kathryn Walters (FORMakademisk, 2021)
As a definition of craft practice, the workmanship of risk emphasises the judgement and skill of the crafter, as they engage with materials, tools, and techniques to produce artefacts. Through experimental design research methods, self-forming three-dimensional textiles were created with the aim to develop both the use of digital and automated tools for weaving, and language to describe the process of textural forming in weaving when hand and machine meet. Examples of experimental work illustrate the potential of industrial looms as tools for crafting complex textile systems and expressions. The results include a method for crafting at the intersection of the workmanship of risk and CAD/CAM, providing a framework for this hybrid practice, while a new language of textile forming for craft including industrial and CAD/CAM tools emerges.